What drives Indonesian companies to engage in ESG: The non-financial corporate context - Dini, Fanji Indra Julian; Dahlan, Muhammad; Hasyir, Dede Abdul (International Journal of Financial, Accounting, and Management, 2025)
Purpose: This study aims to determine how managerial myopia and financial distress affect ESG performance through earnings management. Methodology/approach: The PLS-SEM approach was used to examine secondary data in this quantitative investigation. This study uses data from non-financial companies listed on the IDX from 2013-2022. Results/findings: This study discovered that financial distress improves the company's ESG performance as seen through earnings management, but this effect is insignificant. Meanwhile, managerial myopia has a negative and insufficient effect on ESG performance as seen through earnings management. Separate research revealed that managerial myopia and financial distress had a detrimental impact but not significant on ESG performance. Conclusion: Companies facing financial distress tend to reduce ESG involvement, while myopic managers prioritize short-term outcomes over sustainability practices. Earnings management weakens ESG performance, and both financial distress and managerial myopia fail to significantly drive ESG engagement in Indonesian firms. Limitations: Due to the limitations of research data, especially data on research and development (R&D), this study cannot compare ROA, marketing, and R&D performance to measure managerial myopia. This study does not further investigate whether the low motivation of companies towards ESG caused by financial distress and managerial myopia affects the company's financial performance. Contribution: This research contributes to deepening understanding of the negative impacts of financial distresses and managerial myopia as well as the effects of earnings management on corporate sustainability.